Evidence for different episodes of aeolian construction and a new type of wind streak in the 2016 ExoMars landing ellipse in Meridiani Planum, Mars. Issue 4 (22nd April 2015) - Silvestro, S.; Vaz, D. A.; Di Achille, G.; Popa, I. C.; Esposito, F.
Abstract We present evidence for a complex, multigenerational bed form pattern and a new type of wind streak (the ripple streak) in the landing site ellipse of the 2016 ExoMars Entry descent and landing Demonstrator Module (EDM) in Meridiani Planum (Mars). We identified three main groups of bright‐toned bed forms. Population 3, represented by NE‐SW trending bed forms located inside craters, was emplaced by winds coming from the NW or the SE. Population 2, emplaced by strong easterlies, formed by intracrater transverse aeolian ridges (TARs) and N‐S trending megaripples (plains ripples). Population 1 consists of a relict bed form pattern emplaced by winds coming from the north or south. Alternatively, population 1 can represent a sand ribbon pattern that formed together with the plain ripples. We also report the presence of a new type of wind streak, the ripple streak, which is formed by the population 2 bed forms clustered in the wake zone of impact craters. Based on the results of this work, we now know the EDM module is set to land in a complex aeolian environment. Data from the Dust Characterization, Risk Assessment, and Environment Analyser on the Martian Surface onboard the EDM can help to better decipher the wind regime in Meridiani Planum.